Understanding the Interaction Between Oligopeptide and Water in Aqueous Solution Using Temperature-Dependent Near-Infrared Spectroscopy. Issue 9 (September 2018) - Cheng, Dan; Cai, Wensheng; Shao, Xueguang
Investigating the interaction between oligopeptide and water is essential for understanding the structure, dynamics and function of proteins. Temperature-dependent near-infrared (NIR) spectroscopy and independent component analysis (ICA) were employed to study the interaction between oligopeptide and water in aqueous solution. The NIR spectra of two homo-oligopeptides, penta-aspartic acid (D5 ) and penta-lysine (K5 ), in aqueous solution of different concentration were measured at different temperature (30–90 ℃). Independent component analysis was performed to extract the spectral information that changes with temperature. The independent components (ICs) representing the spectral information of NH and CH2 groups were obtained. Compared with D5, the two groups in K5 change significantly at higher temperature. The result may suggest that K5 has stronger interaction with water than D5 . Moreover, three ICs that contain the spectral information of the water species with no (S0 ), one (S1 ), and two (S2 ) hydrogen-bonds were obtained. It was shown that the spectral intensity of S0 and S1 increases while that of S2 decreases with the temperature, and the changes of oligopeptide solutions are weaker than those of pure water. The results indicate that water structure is sensitive to temperature and the oligopeptide in aqueous solution improves the thermal stability of the water species. When oligopeptide is added, the spectral intensity of S0 and S2 decreases and that of S1 increases for D5 solution, but the intensity of all the three species decreases for K5 solution. Furthermore, the concentration effect of K5 was found to be stronger than D5 . The result may reveal that D5 combines with water molecule through forming one hydrogen bond but K5 interacts with water through a different way.